Tell el-Retaba in the 1st Millennium BC. Results of the Polish-Slovak Archaeological Mission, season 2019 - Jarmużek, Łukasz (Ägypten und Levante, 2020)
In 2019, the Polish-Slovak Archaeological Mission in Tell el-Retaba continued the excavation of a large fragment of a Third Intermediate Period settlement. Several houses, as well as structures used for keeping animals were explored. An unexpected discovery of a Greco-Roman tomb added a new chapter to the site’s settlement history.